2011
DOI: 10.1007/s12013-011-9170-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plasma and Cerebrospinal Fluid Levels of Endothelin-1 and No in Reducing Cerebral Vasospasm after Subarachnoid Hemorrhage During Treatment with Mild Hypothermia, in a Dog Model

Abstract: Using vascular heat-exchange controller implemented mild hypothermia treatment, the authors established the cerebral vasospasm model in which blood was injected twice into dog's foramen magnum; and it was discussed the influence of the concentration of endothelin-1 and NO in blood plasma and cerebrospinal fluid through continuing treatment of mild hypothermia at different times in secondary brain vasospasm model after subarachnoid hemorrhage. Thirty healthy mongrel dogs were randomly divided into five groups; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…TH was related to significant reductions of MCA and peak spastic velocities, which may resemble a decreased degree of macrovascular spasm [23] . As previously suggested, TH mediates its neuroprotective effects by modulations of molecular, metabolic and inflammatory processes, possibly supporting associations with cerebral blood flow velocities [6,12,[28][29][30] . Such a mechanistic association of TH seems likely, yet its influence on actual peak spasm and its clinical significance warrant further investigations [31] .…”
Section: Discussionsupporting
confidence: 74%
“…TH was related to significant reductions of MCA and peak spastic velocities, which may resemble a decreased degree of macrovascular spasm [23] . As previously suggested, TH mediates its neuroprotective effects by modulations of molecular, metabolic and inflammatory processes, possibly supporting associations with cerebral blood flow velocities [6,12,[28][29][30] . Such a mechanistic association of TH seems likely, yet its influence on actual peak spasm and its clinical significance warrant further investigations [31] .…”
Section: Discussionsupporting
confidence: 74%
“…Cerebral vasospasm is considered an important cause of DCI and can partly be explained by the mismatch between vasodilatatory and -constrictor substances as well as detrimental effects of SAHrelated inflammatory reactions [44]. Animal studies have shown the potentially beneficial effects of hypothermia on cerebral vasospasm [3,4,7]. Further-more, we previously demonstrated the attenuation of inflammatory reactions during combined hypothermia and barbiturate coma in patients with severe SAH [45].…”
Section: Discussionmentioning
confidence: 84%
“…Studies have shown an imbalance between the release of nitric oxide (vasodilator) and endothelin-1 (vasoconstrictor) and higher baseline levels of endothelin-1 in the plasma of subjects with SCF [6,19,20,27]. The correlation of a high hematocrit with SCF might be because increased blood viscosity impairs the endothelial release of vasoactive substances, and the imbalance between the release of nitric oxide and endothelin-1 may have a pathophysiologic role in SCF.…”
Section: Discussionmentioning
confidence: 99%